2012
DOI: 10.1177/175045891202200902
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Blood Tests in Elective General Surgery: Cost and Clinical Implications

Abstract: A retrospective observational study was performed in our trust in October 2010 that examined compliance, and the financial and clinical implications of performing inappropriate preoperative blood tests on adult patients prior to elective surgery, against the 2003 NICE guidelines. An unacceptable proportion of inappropriate tests (31.3%) were being performed. None were associated with adverse outcome or changes in management. Based on our results, we estimate that an extrapolated cost of pound 11.2 million is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
(42 reference statements)
0
2
0
1
Order By: Relevance
“…Similarly, in a study of 1496 patients in Thailand, Siriussawakul et al found that only 12.1% of patients had preoperative workups that were in accordance with guidelines, with CMP/electrolytes being the most commonly ordered unnecessary test ( 26 ). In the UK, Phoenix et al estimated that inappropriate preoperative blood work resulted in an extrapolated cost of £11.2 million per year ( 28 ). In the United States, a similar trend is noted.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a study of 1496 patients in Thailand, Siriussawakul et al found that only 12.1% of patients had preoperative workups that were in accordance with guidelines, with CMP/electrolytes being the most commonly ordered unnecessary test ( 26 ). In the UK, Phoenix et al estimated that inappropriate preoperative blood work resulted in an extrapolated cost of £11.2 million per year ( 28 ). In the United States, a similar trend is noted.…”
Section: Discussionmentioning
confidence: 99%
“…Diferentes autores y guías clínicas [82][83][84][85][86][87] advierten y establecen recomendaciones en contra de la solicitud de pruebas analíticas prequirúrgicas de manera rutinaria, recomendando en su lugar realizar una buena historia clínica en el estudio prequirúrgico, y solicitando aquellas pruebas necesarias individualizando en función de las características del paciente, así como de la intervención. Fundamentan este hecho en la baja probabilidad de que exista alguna enfermedad no diagnosticada que comprometa el periodo perioperatorio en pacientes clínicamente asintomáticos.…”
Section: Solicitud De Pruebas Analíticas En El Preoperatoriounclassified
“…Mostly these tests are requested without specific indication based on history or physical examination but rather on speculations that the anaesthetist may "require them" to proceed with the surgery and thus avoid delays and cancellations Routine pre-operative test results in significant cost to the hospital and expense for the patient. The cost of a single laboratory test may be negligible but too many tests have increased cost for many national health schemes [8] [9]. An unnecessary preoperative investigation adds a lot of cost to both the patient and insurance schemes, some of these laboratory investigations are not covered under the health insurance scheme thereby adding to the cost of surgery even if the patient is insured.…”
Section: Introductionmentioning
confidence: 99%